1991
DOI: 10.1109/61.97736
|View full text |Cite
|
Sign up to set email alerts
|

A survey of harmonic voltages and currents at distribution substations

Abstract: This paper reports seven day measurements of harmonic current and voltage made at the sending end of jive feeders. The major goals are to present different ways of recording and displaying harmonics, to explain the results and to compare them with the existing engineering recommendations. At the same time, these results will provide the initial core of documentation for future reference and followup of the harmonic growth trend in 15 and 25kV feeders.The need for information on levels of harmonic pollution in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(26 citation statements)
references
References 2 publications
0
23
0
3
Order By: Relevance
“…Deve ainda ser lembrado que com o avanço tecnológico das últimas décadas e o aumento considerável da utilização de sistemas eletrônicos em equipamentos e máquinas, intensificou-se a preocupação com as variações de freqüên-cia no sistema, uma vez que estes modernos componentes são mais sensíveis a este tipo de perturbação (Emanuel et al, 1991). Deste modo, observa-se que o aprimoramento das técnicas utilizadas para uma melhor estimação da flutuação da freqüência em um SEP é muito importante para a operação correta do mesmo.…”
Section: Introductionunclassified
“…Deve ainda ser lembrado que com o avanço tecnológico das últimas décadas e o aumento considerável da utilização de sistemas eletrônicos em equipamentos e máquinas, intensificou-se a preocupação com as variações de freqüên-cia no sistema, uma vez que estes modernos componentes são mais sensíveis a este tipo de perturbação (Emanuel et al, 1991). Deste modo, observa-se que o aprimoramento das técnicas utilizadas para uma melhor estimação da flutuação da freqüência em um SEP é muito importante para a operação correta do mesmo.…”
Section: Introductionunclassified
“…Emanuel, Orr, Cyganski and Gulachenski [7] reported on measurements on 5 distribution feeders. They show that the significant harmonic voltage levels are occurring on these systems at the third, fifth, and seventh harmonics.…”
Section: Distributed Harmonic Sourcesmentioning
confidence: 99%
“…This method must account for the unknown magnitude and location of the harmonic sources as well as the changes in the system operating configuration which will be encountered. There is an immediate need for this methodology as a number of recent studies have reported harmonic voltages at or near levels where filtering is desirable [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In other line of research, the data collected by Emanuel et al (1991 in extensive surveys, was used by Cavallini et al (1995) to propose a deterministic-stochastic approach to calcu-late the Probability Density Function (PDF) resulting from the sum of harmonic currents in distribution network buses. The novelty of this work lies in considering the variation patterns of harmonics over time from a deterministic component, coupled to a component which takes into account the randomness of distortion.…”
Section: Caicedo Romero and Zinimentioning
confidence: 99%